The Influence of Project-Based Complex Instruction (CI) Collaborative Learning Models and Learning Motivation on Elementary School Students’ Problem Solving Skill - Eges Triwahyuni; Bahriyatin; Kustiyowati (Postgraduate, University of Mataram, 2024)
The problems solving skills of class V students in mathematics learning are still relatively low. One of the things that causes this is the teacher's tendency to carry out learning conventionally through lecture, question and answer and assignment methods. Teachers have a dominant role in finding, processing and explaining the material being taught. Students are not given the freedom to elaborate on the material taught through collaboration with their peers. The objectives of this research are: to describe the influence of the project-based CI Collaborative Learning Model on students' problems solving skills; Describe the interaction between the project-based CI Collaborative Learning Model and learning motivation on students' problems solving skills. The research method used was Quasi Experiment with a Nonequivalent Pretest-Posttest Only Control Group Design. The research instruments used were problem solving skills tests and learning motivation questionnaires. The results of the homogeneity test and normality test of problems solving skill show that the sample variance is homogeneous and normally distributed. After fulfilling the prerequisite tests, a hypothesis test is carried out and it can be concluded that the project-based CI Collaborative Learning Model has a significant effect on students' problems solving skills. Apart from that, there is no interaction between the project-based CI Collaborative Learning Model and learning motivation on students' problems solving skills